Integrating single-cell and spatial transcriptomics reveals the cellular heterogeneity of vestibular schwannoma - Wenqi Dong; Yuchen Jin; Lingkang Dong; Yumeng Jiang; Zhuangzhuang Li; Maoxiang Xu; Jingjing Wang; Feng Liu; Dongzhen Yu (npj Precision Oncology)
Abstract Vestibular schwannoma (VS) is a benign tumor that can result in significant neurological and otological complications. The mechanisms underlying its development and spatial heterogeneity remain poorly understood. In this study, we analyzed single-cell RNA sequencing (scRNA-seq) data from three previously published vestibular schwannomas (VS1-3), along with spatial transcriptomics data from two additional specimens (VS_S1-2). Our results identified a VEGFA-enriched Schwann cell (SC) subtype in scRNA-seq data, which was validated by spatial transcriptomics. This subtype also exhibited a significant positive correlation with NOV hi SCs expression. These cells were centrally localized within tumor tissue. Furthermore, spatial analysis provided new insights into SC-stromal cell interactions, and we constructed a preliminary cellular atlas of VS tissues, enhancing our understanding of tumor growth dynamics.